2016
DOI: 10.1097/id.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

New Osseodensification Implant Site Preparation Method to Increase Bone Density in Low-Density Bone

Abstract: Purpose:The aim of this study was to evaluate a new surgical technique for implant site preparation that could allow to enhance bone density, ridge width, and implant secondary stability.Materials and Methods:The edges of the iliac crests of 2 sheep were exposed and ten 3.8 × 10-mm Dynamix implants (Cortex) were inserted in the left sides using the conventional drilling method (control group). Ten 5 × 10-mm Dynamix implants (Cortex) were inserted in the right sides (test group) using the osseodensification pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
183
1
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(210 citation statements)
references
References 31 publications
(34 reference statements)
10
183
1
16
Order By: Relevance
“…Other examples include geometrical configuration, implant surface characteristics such as texture, composition, or degree of porosity . In addition to the aforementioned geometrical configurations, recent work has indicated that drilling protocols that differ from conventional subtractive drilling methods not only improve implant initial stability but also contributes to faster osseointegration …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples include geometrical configuration, implant surface characteristics such as texture, composition, or degree of porosity . In addition to the aforementioned geometrical configurations, recent work has indicated that drilling protocols that differ from conventional subtractive drilling methods not only improve implant initial stability but also contributes to faster osseointegration …”
mentioning
confidence: 99%
“…Conventional drilling protocols utilize a cutting (subtractive) technique in a clockwise direction with a positive rake angle resulting in the absence of bone residue in the osteotomy, while the non‐cutting (additive) drilling technique, osseodensification (OD), has been shown to compact osteotomy site walls by means of lateral displacement of bone, thus increasing primary stability . Furthermore, the compacting of residual bone remnants, which act as nucleating surfaces for osteoblasts around the implant, function as an autograft facilitating osseointegration …”
mentioning
confidence: 99%
“…Contact area increased with bone densification for the blunt extraction broach only. The exact mechanism for this is not clear, but the small tooth height of the blunt extraction broaches may cause trabecular spaces to be filled up with the bone debris from broaching . This may result in enhanced long‐term stability of the prosthesis, since bone debris plays a supporting role in osseointegration …”
Section: Discussionmentioning
confidence: 99%
“…Duncan [3] refers to noncritical size defects in the posterior mandible, and the use of the posterior mandible for implant placement following extraction of premolar teeth. The paper by Trisi et al [15] refers to implant placement in the sheep iliac crest.…”
Section: Abstract: Osteoporotic Sheep Model Bone Densification Qualmentioning
confidence: 99%